2011
DOI: 10.1371/journal.pone.0025296
|View full text |Cite
|
Sign up to set email alerts
|

How to Change the Oligomeric State of a Circular Protein Assembly: Switch from 11-Subunit to 12-Subunit TRAP Suggests a General Mechanism

Abstract: BackgroundMany critical cellular functions are performed by multisubunit circular protein oligomers whose internal geometry has evolved to meet functional requirements. The subunit number is arguably the most critical parameter of a circular protein assembly, affecting the internal and external diameters of the assembly and often impacting on the protein's function. Although accurate structural information has been obtained for several circular proteins, a lack of accurate information on alternative oligomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…The scenario found in the 12-mer B. halodurans TRAP, regarding the exclusion of the C-terminus, could logically be mimicked by truncating the 4 or 5 C-terminal residues, removing this segment from the subunit interface. This is observed in the previously determined structures of B. stearothermophilus E71stop TRAP and B. subtilis K71stop TRAP [9]. With respect to thermal stability accompanying the 11-mer to 12-mer transition, we find that this truncation results in an increase in melting temperature, so that at 50 µM L-tryptophan the increase in melting temperature between B. stearothermophilus wild type and E71stop is 6°C, from 81.4°C to 87.4°C.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The scenario found in the 12-mer B. halodurans TRAP, regarding the exclusion of the C-terminus, could logically be mimicked by truncating the 4 or 5 C-terminal residues, removing this segment from the subunit interface. This is observed in the previously determined structures of B. stearothermophilus E71stop TRAP and B. subtilis K71stop TRAP [9]. With respect to thermal stability accompanying the 11-mer to 12-mer transition, we find that this truncation results in an increase in melting temperature, so that at 50 µM L-tryptophan the increase in melting temperature between B. stearothermophilus wild type and E71stop is 6°C, from 81.4°C to 87.4°C.…”
Section: Discussionsupporting
confidence: 77%
“…The tryptophan RNA-binding attenuation protein, TRAP, possesses similar geometric features to other circular assemblies, being assembled of multiple subunits and containing a central tunnel. Typically composed of 11 or 12 identical subunits, with a molecular weight of 90.6 to 101.9 kDa [8] , [9] , TRAP regulates L-tryptophan biosynthesis genes by attenuation in many Bacilli [10] . When activated by increased levels of L-tryptophan – bound to receptor sites nestled between adjacent subunits – TRAP binds single stranded RNA at the leader region of the trpEDCFBA operon transcript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller population of the 12-mer TRAP compared with the 11-mer is primarily attributed to subtle differences in the inter-subunit interactions. Antson et al [32] recently found that B. halodurans TRAP exclusively forms a 12-mer ring. The crystal structure of the 12-mer B. halodurans TRAP showed the C-terminal residues with a conformation different from those of the 11-mer TRAP of B. subtilis or B. stearothermophilus , which forms different interactions with the adjacent subunit allowing an increase in the diameter of the ring [32].…”
Section: Discussionmentioning
confidence: 99%
“…Antson et al [32] recently found that B. halodurans TRAP exclusively forms a 12-mer ring. The crystal structure of the 12-mer B. halodurans TRAP showed the C-terminal residues with a conformation different from those of the 11-mer TRAP of B. subtilis or B. stearothermophilus , which forms different interactions with the adjacent subunit allowing an increase in the diameter of the ring [32]. However, the present study shows that symmetry significantly influences dynamics, and should be another important factor for not only stability but also biological function (for example, ligand binding) of ring proteins, especially for large ring structures like the present case of C 11 and C 12 .…”
Section: Discussionmentioning
confidence: 99%